Diversity of Pollinating Insects in Antigonon leptopus at PTPN IV Kebun Melati Perbaungan and Its Development as a Monograph Book for Biology Learning - Riza Sibuea; Sularno Sularno; Edi Azwar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
Pollinator insects have a crucial ecological role in supporting the reproduction of flowering plants and maintaining ecosystem balance, especially in oil palm plantation agroecosystem areas. This study aims to analyze the diversity of pollinating insects in Bridal Tear flowers (Antigonon leptopus) at PTPN IV Kebun Melati Perbaungan and develop the results of the research into a monograph book for biology learning. The research was carried out for three months (January-March 2026) at three observation stations using an exploratory survey method using a sweeping net. The results of the study found 179 individuals of pollinating insects classified into 7 species, 7 genera, 5 families, and 2 orders (Hymenoptera and Lepidoptera). Species identified include Apis cerana, Xylocopa latipes, Vespa affinis, Suastus gremius, Neptis hylas, Graphium sarpedon, and Cepora nerissa. Analysis of the ecological index showed moderate diversity values (H'=1.884), high uniformity (E=0.968), and low dominance (D=0.159), indicating a relatively stable community structure. The highest abundance is found in the morning and evening. This study concludes that Antigonon leptopus plays an important role as a source of food for pollinating insects and the results of the research have the potential to be developed as a monograph book to support biology learning.